Putative mechanisms of bacterial effects on plant photosystem under stress - Burlak, O.P.; de Vera, J.-P.; Yatsenko, V.; Kozyrovska, N.O. (Вiopolymers and Cell, 2013)
Bacteria are micro- and nanoorganisms that spatially colonize the plant organism and comprise various types of interactions with the host ranging from pathogenic to mutualistic and symbiotic. The presence of these exo- and endosymbionts may affect the plant host physiology. Non-pathogenic bacteria can enhance defensive capacity in plants that provides protection against phytopathogens and herbivores, as well as makes a valuable contribution to the protection of plants from abiotic stressors. Endophytes demonstrate the protection of photosystem in plants under environmental challenges. The putative mechanisms of bacterial effects on plant photosystem are discussed in this paper. Бактерії є мікро- і наноорганізмами, які колонізують простір рослинного організму і укладають різні види взаємодій – від патогенних до мутуалістичних і симбіотичних. Присутність цих екзо- та ендосимбіонтів може впливати на фізіологію рослини-господаря. Непатогенні бактерії здатні посилювати у рослин функції захисту від фітопатогенів і шкідників, а також опірність дії абіотичних стресорів. Ендофіти перешкоджають шкідливим ефектам довкілля на фотосистеми рослин. Ймовірні механізми подібного впливу обговорюються у даній статті. Бактерии являются микро- и наноорганизмами, колонизирующими пространство растительного организма и формирующими различные виды взаимодействий – от патогенных до мутуалистических и симбиотических. Присутствие этих экзо- и эндосимбионтов может влиять на физиологию растения-хозяина. Непатогенные бактерии способны усиливать у растений функции защиты от фитопатогенов и вредителей, а также устойчивость к действию абиотических стрессоров. Эндофиты противостоят вредному воздействию окружающей среды на фотосистемы растений. Возможные механизмы подобного влияния обсуждаются в данной статье.